Geoquímica de sedimentos lacustres em sistemas com elevadas taxas de sedimentação por eventos climáticos extremos: estudos de caso na República Dominicana - Araújo, Joana (2021)
The climate of Dominican Republic is a humid tropical climate,with periodic annual occurrence of hurricanes. The climate, in association with a rugged topography, represent factors that enhance high erosion rates and, consequently, high sedimentation rates. This sedimentation excess contributes to the silting of the reservoirs, and are responsible for the reduction of the hydroelectric power production and of the potential of water storage. The aim of our study is to do a geochemical characterization of major and trace elements, including the REE, of the bottom sediments of two chosen dams, and to evaluate their sources through a comparative study with the soils of the drainage basins. It is also intended to determine the real influence of each drainage sub-basin in the sedimentation process of these systems. The two selected dams are Tavera and Sabana Yegua, which are limited by the central mountain range, being Tavera at North and Sabana Yegua at South. The sediment sampling was carried out in two seasonal periods, at representative locations of the different hydrodynamic conditions of each reservoir, through dredging of the surface layer. Soil sampling was performed in a single campaign, in several sectors of the respective drainage basins. The sampling was followed by analysis of major and trace elements by ICP-OES, organic carbon and sulfur by an elemental analyzer, and textural characteristics of both, sediments and soils. The achieved geochemical data allowed a comparative study between the sediments of the dams and the soils of the drainage basins, through multielementar correlation analysis relatively to the contents of major and trace elements and to the granulometric fractions, in order to identify the sediments provenance. Although lithotypes are very similar in both basins (characterized by volcano-sedimentary rocks of arch-island origin, tonalites, sandstones, conglomerates and intermediate volcanic rocks), the main difference between the two basins is that Sabana Yegua reservoir and a part of its tributaries are inserted into sedimentary, detrital and carbonate formations. The geochemical data is very homogeneous throughout the whole area of the reservoirs, allowing to verify the occurrence of uniform sedimentation in both cases, which reflects a high hydrodynamism. The soils show a higher heterogeneity as result of their sampling had been done at different sectors of those basins. This study is in a preliminary state, in a near future we are going to perform the same geochemical analysis in rocks, and analysis of REE in sediments, soils and rocks.